2013
DOI: 10.1080/13607863.2013.856860
|View full text |Cite
|
Sign up to set email alerts
|

‘Getting to Know Me’: the development and evaluation of a training programme for enhancing skills in the care of people with dementia in general hospital settings

Abstract: The 'Getting to Know Me' programme was well received and had a significant impact on staff knowledge and confidence. Our findings add to a growing evidence base which will be strengthened by further robust studies, the exploration of the impact of staff training on direct patient outcomes, and further identification of ways in which to transfer principles of care from specialist dementia environments into general hospital settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
170
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(177 citation statements)
references
References 22 publications
7
170
0
Order By: Relevance
“…This supports findings from previous studies (Banks et al, 2014, Elvish et al, 2013, Galvin et al, 2012 which have demonstrated similar results.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This supports findings from previous studies (Banks et al, 2014, Elvish et al, 2013, Galvin et al, 2012 which have demonstrated similar results.…”
Section: Discussionsupporting
confidence: 93%
“…Using a non-validated questionnaire at each time point they found the training had an immediate impact on staff knowledge, competence and attitudes and that this was largely maintained over the 120 day period of time. Likewise, in a UK pre-post design study, Elvish et al (2013) found that in a sample of 71 general hospital staff who completed a 6-hour dementia training programme, knowledge about dementia, confidence in providing care to this group and beliefs about 'challenging behaviour', assessed using validated measures, significantly improved. Banks et al (2014) implemented a blended learning dementia champions programme comprised of 5 study days alongside a half day in a community care setting, with 100 staff working at an 'enhanced level' in acute settings.…”
Section: Background To the Studymentioning
confidence: 95%
“…Our review suggests training that would be of particular benefit: i) would be tailored specifically for general hospital ward environments; ii) would improve confidence; iii) would shift perceptions about the causes of challenging behaviour; iv) would help staff to view their job role as addressing the needs of people with dementia. Although limited, evidence from recent studies suggests that dementia training programmes undertaken within general hospitals can improve staff knowledge and confidence (Elvish et al, 2014;Galvin et al, 2010) and shift staff towards more personcentred perspectives regarding behaviours that challenge (Elvish et al, 2014). Further studies to investigate this would be of benefit and focus must also now turn to investigate the impact of training on direct patient care.…”
Section: Clinical and Research Implicationsmentioning
confidence: 99%
“…Similarly, Turner, Eccles, Elvish, Simpson & Keady (2015) recommended that dementia care training should be specifically tailored for hospital wards and should evaluate patient outcomes once completed; since most of the studies to date focus mainly on staff outcomes (Elvish et al, 2014, Galvin et al, 2010.…”
Section: Dementia Care Training and Educational Interventions In Clinmentioning
confidence: 99%